Optimization of quality of functional improvement – aspects of psychomedical treatment - Szerla, Małgorzata K.; Wąsik, Jacek; Ortenburger, Dorota E.; Gwara, Michał; Trybulec, Bartosz (Medical Studies/Studia Medyczne, 2016)
Literature on the subject and clinical practice indicate that the improvement of an individual’s psychophysical functioning encourages multiplying and strengthening positive therapeutic effects. Approaches of Western and Eastern culture (selected aspects) have been included in deliberations on this issue. The purpose of this study was to adopt a multi-dimensional approach to improving functional efficiency through optimizing locomotion in the comprehensive treatment of the patient. The paper is the authors cognitive analysis based on the literature on the subject, including each author’s own approach to clinical practice located at the interface of medicine, physiotherapy and psychology. Optimal functioning improvement considering the individual context of each patient is a common objective of the interdisciplinary therapeutic interaction. Obtaining maximum effectiveness in therapy is associated with enormous effort, complex skills, predisposition and other factors, which are the subject of growing scientific knowledge.